A Perancangan Kampanye Sosial Detoksifikasi Upaya Menghindari Kecanduan Pengguna Media Sosial Dengan Media Motion Graphic - Nurrahmahdani, Hani; Noor, Abidin M; Kusumawati, Desiana Nur Indra (Jurnal Ilmiah Wahana Pendidikan, 2024)
Dependence on social media is a condition in which a person becomes very dependent on using social media platforms, and feels uncomfortable when they cannot access them. Individuals who experience this often feel the need to stay connected to their phones so as not to feel alienated from friends and the latest information on social media. The main motivation behind this behavior is getting recognition or attention from others. This pattern repeats itself incessantly, with social media becoming an integral part of daily routines on a large scale. Research on this issue uses a qualitative approach that focuses on deep understanding of the social challenges that arise as a result of this situation. The main objective of this qualitative research is to understand this social phenomenon by clearly describing the experiences and symptoms that arise through the use of words, which in turn can produce a more comprehensive theory. So media is needed that provides understanding and education on how to respond so you don't depend on social media. The media is a motion graphic that is packaged into a public service advertisement, in order to make social media users aware. With the existence of public service advertisements through motion graphic media, social media users are aware of trying to control themselves and avoid social media addiction. Through this public service advertisement video work with motion graphics, this is the first step in changing the way of introducing and also learning about digital detoxification to the mass audience.